Age and Growth of Redfish (Sebastes marinus, S. mentella and S. fasciatus) in Flemish Cap (Northwest Atlantic) - Saborido-Rey, Fran (Northwest Atlantic Fisheries Organization, 2001)
19 páginas, 5 figuras, 13 tablas.-- Deep-sea Fisheries Symposium – Oral, September 2001. Ageing of redfish is one of the major problems within the research related with redfish. In this paper it is validated the age readings of S. mentella in Flemish Cap following the most important year-classes along the last 13 years. The criteria used for S. mentella looks consistent and coherent. Growth of different S. mentella cohorts is described and compared observing the existence of a remarkably density-dependence growth in the strong 1990 year-class, which performed a slowest growth rate. This reduction in growth rate has prevented that this cohort become mature at expected age. Then growth was compared between sexes both in S. mentella, S. marinus and S. fasciatus showing that females grow faster than males. Finally the growth rate is compared among species. S. marinus displayed the fastest growth and S. mentella the lowest, although the mentioned density-dependence in S. mentella has to be considered in the comparison. Peer reviewed